Lectin Histochemical Study of GalNac and GlcNac Containing Glycoconjugates in Colon Adenocarcinoma - Mohamad Reza Arab; Ali Reza Rojhan; Mehdi Jahantigh; Mehdi Mohammadi (Anatomical Sciences Journal, 2013)
Introduction: Alteration of terminal sugars of Glycoconjugates is one of the important aspects of neoplasia. The aim of the present study was to identify GalNac and GlcNac containing glycoconjugates in different grades of neoplastic cells in adenocarcinoma of colon.